2015
DOI: 10.1021/acs.orglett.5b01229
|View full text |Cite
|
Sign up to set email alerts
|

Directed Amination of Aryl Methyl Ethers Mediated by Ti(NMe2)4at Room Temperature

Abstract: An efficient C-O amination of aryl methyl ethers has been achieved. This transformation proceeds via imine-directed Ti(IV)-mediated cross-coupling reactions between aryl methyl ethers and Ti(NR2)4 at room temperature, straightforwardly leading to a series of arylamines. This protocol features a wide substrate scope, exclusive regioselectivity, and mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…The chemistry of titanium complexes generated by the reactions between Ti­(NMe 2 ) 4 and protonated ligands has been well developed. , It was found that Ti­(NMe 2 ) 4 could mediate the C–N and C–C bond formation reactions. , Treatment of Ti­(NMe 2 ) 4 with HL1 in toluene afforded (dimethylamido)titanium complex Ti­(L1′)­(NMe 2 ) ( 1 ) (Scheme , H 3 L1′ = N1-(2-((2-(1-(dimethyl amino)-1-hydroxy-3-oxoisoindolin-2-yl)­ethyl)­(2-hydroxybenzyl)­amino)­ethyl)-N2,N2-dimethylphthal-amide), which was isolated as a pure red solid after recrystallization in toluene.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The chemistry of titanium complexes generated by the reactions between Ti­(NMe 2 ) 4 and protonated ligands has been well developed. , It was found that Ti­(NMe 2 ) 4 could mediate the C–N and C–C bond formation reactions. , Treatment of Ti­(NMe 2 ) 4 with HL1 in toluene afforded (dimethylamido)titanium complex Ti­(L1′)­(NMe 2 ) ( 1 ) (Scheme , H 3 L1′ = N1-(2-((2-(1-(dimethyl amino)-1-hydroxy-3-oxoisoindolin-2-yl)­ethyl)­(2-hydroxybenzyl)­amino)­ethyl)-N2,N2-dimethylphthal-amide), which was isolated as a pure red solid after recrystallization in toluene.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous report, we disclosed that the −NMe 2 group of Ti­(NMe 2 ) 4 could activate C–O bond . We anticipate that the CO bond and the C–N bond of an amide might be activated by the −NMe 2 group of Ti­(NMe 2 ) 4 too.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…R f (20% hexane in DCM) 0.48; ν max /cm –1 1683, 1594, 1482, 1450; 1 H NMR (400 MHz, CDCl 3 ) 10.4 (1H, s, C H O), 7.80 (1H, dd, J 7.7, 1.8, C(6) H ), 7.49 (1H, ddd, J 8.2, 7.2, 1.8, C(4) H ), 7.15 (1H, d, J 8.2, C(3) H ), 7.13–7.03 (1H, m, C(5) H ), 3.18 (4H, q, J 7.1, C(1′) H ), 1.05 (6H, t, J 7.1, C(2′) H ); 13 C­{ 1 H} NMR (100 MHz, CDCl 3 ) 192.3 ( C HO), 154.7 ( C (2)), 134.4 ( C (4)), 130.9 ( C (1)), 129.0 ( C (6)), 122.4 ( C (5)), 121.8 ( C (3)), 49.0 ( C (1′)), 12.4 ( C (2′)); HRMS (CI + ) m / z : [MH] + Calcd for C 11 H 16 NO 178.1226; found 178.1234. Experimental data is in agreement with reported values …”
Section: Methodsmentioning
confidence: 99%